Predictors of Quality of Life in Mothers of Premature Infant - Hyosin Choi; Yeonghee Shin (Korean Society of Women Health Nursing, 2017)
PURPOSE: The purpose of this study was to determine the factors that may affect quality of life of mothers who delivered premature infants. METHODS: With survey design, data were collected from 145 mothers of premature infants with corrected age of 2 months to 12 months from January 9 to February 2, 2017. Quality of life was assessed with two measures of direct survey in the selected hospital and online survey. A self-report questionnaire was administered regarding personality of the mothers and the infants, postpartum depression, parenting stress, social support, and the quality of life. Data were analyzed using t-test, ANOVA, Pearson correlation coefficients, and multiple regression. RESULTS: The quality of life of the mothers of the premature infants was influenced by postpartum depression, parenting stress, parents-infant dysfunctional interactions, and social support accounted for 65% of the variance. CONCLUSION: These results indicate that early screening and continuous management of postpartum depression during postpartum period are important to improve the quality of life of the mothers of the premature infants. Education program and information and social support systems need to be developed to monitor mother-infant interaction and their role development.